Characteristics and prognosis of hepatocellular carcinoma detected in patients with chronic hepatitis C after the eradication of hepatitis C virus: A multicenter study from Japan. Issue 8 (19th November 2015) - Toyoda, Hidenori; Tada, Toshifumi; Tsuji, Kunihiko; Hiraoka, Atsushi; Tachi, Yoshihiko; Itobayashi, Ei; Takaguchi, Koichi; Senoh, Tomonori; Takizawa, Daichi; Ishikawa, Toru; Kumada, Takashi
Abstract: Aim: We investigated the characteristics and prognosis of patients with hepatocellular carcinoma (HCC) diagnosed after sustained virological response (SVR) to antiviral therapy for chronic hepatitis C virus (HCV) infection, namely, the eradication of HCV, according to surveillance status after SVR. Methods: In this multicenter study, liver function at HCC diagnosis and progression of HCC among patients with HCC diagnosed after SVR were compared. Outcomes were also investigated. Results: In patients not under surveillance after SVR, HCC was significantly more advanced at diagnosis, with tumors that were larger in size and of higher stage than in patients who continued under surveillance after SVR. Survival rates were significantly lower in patients not under surveillance ( P < 0.0001). Among patients who were under surveillance, those with a 6‐month surveillance interval had larger and higher stage HCC than patients with a 3‐month interval. Recurrence rates in patients with a 6‐month surveillance interval were significantly higher than in patients with a 3‐month surveillance interval ( P = 0.0417). Conclusion: Lack of surveillance after SVR was obviously associated with more advanced HCC at detection, resulting in poor prognosis. More importantly, there may be a difference in the severity of HCC at diagnosis and prognosis based on the surveillance interval after SVR. Establishing guidelines how to survey patients with chronic hepatitis C after SVR is necessary.